Towards the light : the story of the struggles for liberty and rights that made the modern West - Grayling, A. C. (London: Bloomsbury, 2014)
"In Towards the Light, A.C. Grayling tells the story of the long and difficult battle for freedom in the West, from the Reformation to the Universal Declaration of Human Rights, from the battle for the vote to the struggle for the right to freedom of conscience. As Grayling passionately affirms, it is a story - and a struggle - that continues to this day as those in power use the threat of terrorism in the 21st century to roll-back the liberties that so many have fought and died to win for us. Including an appendix of landmark documents, including the British and American Bills of Rights and the Declaration of the Rights of Man and of the Citizen, the Bloomsbury Revelations edition also includes a new preface by the author reflecting on developments since the book's original publication"--
Machine generated contents note: -- Preface to the Bloomsbury Revelations EditionAcknowledgements1. Setting the ScenePart I: The Demand for Liberty2. The Reformation and the Beginning of Modern Liberty3. Freeing the Mind4. The Fight Against AbsolutismPart II: The Extension of Liberty5. Slaves, Workers, Women and the Struggle for Liberty6. The Liberty Century7. Rights Out of Wrongs8. The Idea of Liberty and the Verge of BetrayalPostscriptAppendices: Landmarks on the Road to Freedom1. The Bill of Rights, 16892. The US Bill of Rights, 17913. Declaration of the Rights of Man and of the Citizen4. The Chartists' 'Six Points' and Petition5. United Nations Universal Declaration of Human RightsNotesBibliographyIndex.
Originally published in 2007.
Includes bibliographical references and index.
Keywords: Liberty; Human rights; Democracy -- Western countries; Civilization, Western; Civilization, Modern; PHILOSOPHY / History & Surveys / Modern; PHILOSOPHY / General